Ghomeshi, l’avant et l’après - Deglise, Fabien (Le Devoir, 2014)
L’ex-animateur-vedette emporte aussi dans sa chute la loi du silence envers les abus sexuels.
Keywords: Bibliographie; Nettoyer

Unspeakable Inequalities: Post Feminism, Entrepreneurial Subjectivity, and the Repudiation of Sexism among Cultural Workers - Gill, Rosalind (Social Politics: International Studies in Gender, State & Society, 2014)
Work in the cultural and creative fields is marked by stark and growing inequalities relating to gender, class, and race/ethnicity. Yet, the same industries are also characterised by an ethos that celebrates openness, egalitarianism, and meritocracy. This paper explores this paradox, focusing in particular on gender inequalities. It argues that there is a need to move beyond the standard conventional explanations for women's under-representation within the creative workforce, which point to female childbearing and childcare as central. Whilst not disputing the significance of motherhood to women's career trajectories, the paper suggests that the repeated focus on maternity is problematic and may close down other areas of potential investigation and critique. The paper suggests that three alternative foci would repay attention in understanding inequalities in the CCI. First, the new, mobile, subtle, and revitalised forms of sexism in circulation urgently require further examination. Secondly, the power of the dominant post feminist sensibility which, in suggesting that “all the battles have been won,” renders inequality increasingly difficult to voice or speak about, demands critique. Thirdly, the new forms of labouring subjectivity required to survive in the field of cultural work may themselves be contributing to the inequalities in the field, by favouring an entrepreneurial individualistic mode that disavows structural power relations. These three aspects of life in the field of cultural work merit further attention and suggest that gender inequality has a variety of different causes, not all located in women's childbearing abilities. Moreover, the paper argues that the very myth of egalitarianism at work in the CCI may itself be a key mechanism through which inequality is reproduced.

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Fortunes of feminism: from state-managed capitalism to neoliberal crisis - Guest, Carly (European Journal of Cultural and Political Sociology, 2014)
Publisher: Routledge _eprint: https://doi.org/10.1080/23254823.2014.948028

Gender then, gender now: surveying women's participation in Australian film and television industries - French, Lisa (Continuum : Journal of Media and Cultural Studies, 2014)
In the Australian audiovisual industries, women are a minority of the personnel in a large number of key creative roles and have considerably lower representation than in the Australian workforce generally. Despite the decline in their participation across several fields, the under-representation of women is not being addressed by these industries. Using findings from current research that includes a major survey of Victorian activity, this article engages with the urgent need for new approaches to thinking about the contribution and innovation of women: culturally, creatively and economically. Benchmarked against the last major study in 1992 (Cox and Laura), pivotal issues examined include barriers to progression, representation by job type and workplace/organizational cultures, along with a consideration of the current successes (relative to other areas) of women in television. Business, cultural and social arguments are made for the importance of gender equity, and an understanding of the contribution and value of women to these industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/10304312.2014.888040
Keywords: Bibliographie; Irina; Nettoyer

Accounting for Space, Place and Identity: GLBTIQ Young Adults’ Experiences and Understandings of Unwanted Sexual Attention in Clubs and Pubs - Fileborn, Bianca (Critical Criminology, 2014)
This article considers the role of space, place and identity in influencing gay, lesbian, bisexual, transgender/transsexual, intersex and queer (GLBTIQ) young adults’ experiences of unwanted sexual attention in licensed venues. It is argued in this article that the roles of space, place and identity are largely absent from theoretical understandings of sexual violence. Gender-based accounts of sexual violence, while important, are unable to fully account for sexual violence that is perpetrated within and against GLBTIQ communities. Drawing on data obtained through a mixed-methods study, in the first half of the article I establish the manner in which GLBTIQ young adults’ unique relationship with licensed venues appears to mediate the ways in which unwanted sexual attention occurring in these spaces is experienced and understood. The second half of this article is concerned with exploring the intersections between unwanted sexual attention and heterosexist violence and abuse in clubs and pubs. I conclude by considering the implications of these findings for theoretical understandings of sexual violence and unwanted sexual attention.
Keywords: Gender Identity; Intimate Partner Violence; Sexual Identity; Sexual Orientation; Sexual Violence

Safe Space: Towards a Reconceptualization (Antipode, 2014)
The term “safe space” dates to the late twentieth century women's movement, but it has since been used in many different contexts. In this paper, we review and analyze historical and contemporary “safe spaces”. These include “separatist” safe spaces in women's, anti-racist, and feminist communities, “inclusive” safe space classrooms, and safe spaces in which (non-human) objects are central. We argue that safe spaces should be understood not through static and acontextual notions of “safe” or “unsafe”, but rather through the relational work of cultivating them. Such an understanding reveals several tendencies. Namely, safe spaces are inherently paradoxical. Cultivating them includes foregrounding social differences and binaries (safe–unsafe, inclusive–exclusive) as well as recognizing the porosity of such binaries. Renegotiating these binaries is necessarily incomplete; a safe space is never completely safe. Even so, we encourage the critical cultivation of safe space as a site for negotiating difference and challenging oppression.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/anti.12089
Keywords: activism; intersectionality; paradoxical space; porosity; safe space; safety

Making Media Work: Cultures of Management in the Entertainment Industries - Johnson, Derek; Kompare, Derek; Santo, Avi (NYU Press, 2014)
In popular culture, management in the media industry is frequently understood as the work of network executives, studio developers, and market researchers-"the suits"-who oppose the more productive forces of creative talent and subject that labor to the inefficiencies and risk aversion of bureaucratic hierarchies. However, such portrayals belie the reality of how media management operates as a culture of shifting discourses, dispositions, and tactics that create meaning, generate value, and shape media work throughout each moment of production and consumption. Making Media Work aims to provide a deeper and more nuanced understanding of management within the entertainment industries. Drawing from work in critical sociology and cultural studies, the collection theorizes management as a pervasive, yet flexible set of principlesdrawn upon by a wide range of practitioners-artists, talent scouts, performers, directors, show runners, and more-in their ongoing efforts to articulate relationships and bridge potentially discordant forces within the media industries. The contributors interrogate managerial labor and identity, shine a light on how management understands its roles within cultural and creative contexts, and reconfigure the complex relationship between labor and managerial authority as productive rather than solely prohibitive. Engaging with primary evidence gathered through interviews, archives, and trade materials, the essays offer tremendous insight into how management is understood and performed within media industry contexts. The volume as a whole traces the changing roles of management both historically and in the contemporary moment within US and international contexts, and across a range of media forms, from film and television to video games and social media.

Putting gender in the mix: employment, participation, and role expectations in the music industries - LEONARD, MARION (The Routledge Companion to Media & Gender, 2014)
Eﬀorts to map women’s participation in the music industries have been hampered by a lack of data. However, available statistics point to a continuing underrepresentation of women in the music industries; and the disparity is particularly acute within certain areas of practice. In 2010 the Performing Rights Society for Music (PRS), the UK’s leading collection society, revealed that women accounted for only 14 percent of their registered music creators and writers. This statistic prompted the PRS Foundation to fund the “Women Make Music” initiative as a way to raise awareness of the gender gap, correct stereotypes, encourage participation, and increase the proﬁle of women creating new music. Research commissioned in 2008 by the Cultural Leadership Programme and publishedas a substantial report, found that in the UK music sector “only 20% of businesses have any form of female representation on the management team and only 10% have an all female team” (Cultural Leadership Programme 2008: 29). According to the report, women in the music sector were generally very underrepresented within positions of responsibility: the average number of female executives per ﬁrm was as low as 0.2. Such evidence of gender inequality in leadership positions within the music industries is by no means unique to the UK. In 2012 the editorial team of the Australasian Music Industry Directory (AMID), in consultation with other industry professionals, ranked for the ﬁrst time the most powerful people in the Australian music industry. The criteria included who has the greatest “ability to ‘shape’ the scene,” along with “their involvement in industry initiatives, overall career accomplishment, economic impact and public proﬁle” (Fitzsimons 2012). The “power list” included 50 places and 56 people (some business partners held joint positions). Only six women appeared on the list, two of whom shared their place with a male colleague; overall, then, women were just under 11 percent. While the list can be critiqued for its partiality, it indicates the music industries’ gender gap. Books on women working in the music industries usually focus on women musiciansand performers, often with the aim of celebrating women’s contribution to the history of popular music (see, for example, Dahl 1984; Gaar 1993; Hirshey 2001; Downes 2012). In documenting women’s experience, ﬁeld research with musicians has shownhow women have established their music careers, from acquiring instruments and learning to play, to performing and navigating the music business (see, e.g., Bayton 1998; Tucker 2000; Reddington 2007; Leonard 2007). A few speciﬁcally highlight women involved in music production and sound engineering (Sandstrom 2000; Smith 2009). Some recent work on women’s changing relationship with music technologies examines how artist-producers (Wolfe 2012) and women involved in the electronic dance music scene (Farrugia 2012) have navigated a gendered sphere of practice which has historically and discursively been associated with masculinity. Music journalism has also been a focus, with critical accounts addressing the work of women music journalists and the gendered discourse of music journalism (McDonnell 1995; Davies 2001; McLeod 2001). While the literature on women musicians, journalists, DJs, and music engineers is growing, the experience of women working in other roles within the music sector is much less well documented. Indeed, Smith (2009: 308) remarks that, except for musicianship, “scholarship on gender segregation in other music industry roles has been meagre. Because of this, the gendered division of labour in the music industry is not yet adequately understood.” This chapter explores how gendered attitudes circulate within the workplace andin what ways they frame work in diﬀerent sectors of the music industries. The plural term “music industries” suggests the chapter is not engaging with a uniﬁed ﬁeld of practice, nor is it concerned only with the recording industry (Williamson and Cloonan 2007). I will draw on interviews with eight women who have worked in artist management, tour management, A&R (artist and repertoire), and concert promotion, although ﬁrst I discuss the contexts in which these women work as a way to establish the extent to which their occupations can be broadly characterized as sex segregated. These women work in largely under-studied but particularly sex-segregated areasof music employment. All eight were based in London, England and ranged in levels of seniority from a booking agent’s assistant to a general manager of a record company. Many of the women had established portfolio careers, having worked in different roles, including radio promotion, international relations, music publishing, and marketing, so had diﬀerent levels of experience in management, A&R, and concert promotion. For example, one participant worked for two years at a junior level in A&R before moving on to develop expertise in other areas, eventually becoming a general manager of a record company. Another participant began as a regional A&R scout and was promoted to A&R manager, where she stayed ten years. Therefore, they could oﬀer a broad perspective: collectively they were engaged with international professional networks, international tour management, and the management and career development of artists building international proﬁles. The majority of them worked with rock bands and artists but some had worked with artists in other genres. The participants could also reﬂect on their experience of working with artists at diﬀerent stages of career development, from new and developing bands through to major international recording stars. Seven of the approximately hour-long interviews were conducted by telephone; their responses to the open-ended questions were recorded and transcribed. One respondent oﬀered a written response to the research questions via email. The women all seemed candid in their responses. Their comments have been anonymized; references to particular record labels, bands, or named individuals have been omitted.
Num Pages: 10